Cohort profile: the Health of Philippine Emigrants Study (HoPES) to examine the health impacts of international migration from the Philippines to the USA - A B de Castro; Anna K Hing; Nanette R Lee; Maria Midea M Kabamalan; Karen Llave; Catherine M Crespi; May Wang; Gilbert Gee (BMJ Open)
Purpose The Health of Philippine Emigrants Study (HoPES) longitudinally investigates over 3 years whether migrating from the Philippines to the USA results in increased risk for obesity relative to non-migrants in the Philippines. The study is designed to test the healthy immigrant hypothesis by collecting health measures from migrants starting from a pre-migration baseline and enrolling a non-migrant cohort matched on age, gender and education for comparison.Participants A migrant cohort (n=832; 36.5% of eligible individuals) was recruited from clients of the Commission on Filipinos Overseas prior to exiting the Philippines. A non-migrant cohort (n=805; 68.6% eligible individuals) was recruited from community households in municipalities throughout the cities of Manila and Cebu. By intention, these two cohorts are comparable demographically, including urban/rural status of residency in the Philippines at baseline.Findings to date At baseline, compared with non-migrants, migrants report significantly better self-rated health and less depression, and have significantly larger hip circumference and lower waist-to-hip ratio, as well as significantly higher mean systolic blood pressure and higher mean level of apolipoprotein B. Baseline results can offer insight into the health status of both migrant and non-migrant populations and may be useful for obesity prevention efforts.Future plans Longitudinal data collection is scheduled to be completed in December 2020 when the final data collection wave (36 months after baseline) will conclude. Both migrant and non-migrant cohorts will be maintained beyond the current prospective study, so long as research funding allows and emerges for new study questions. Findings from future longitudinal analyses can inform the need and design of health-related/relevant interventions, whether clinical, behavioural, educational, or policy, that can be implemented at the individual or population level.